Russia's Iran policy: Global and regional objectives, political and economic interests - Hannes Adomeit (Stiftung Wissenschaft und Politik (SWP), 2006)
Iran's nuclear programs and its putative ambition to build the atom bomb have produced what is generally considered to be at present the most dangerous international crisis. Russia, as a permanent member of the UN Security Council, neighbor of Iran in the Caspian area, and supplier of civilian nuclear technology and conventional weapons, is regarded as having more influence than any other international actor in Tehran. But what drives the Kremlin's policies in the dispute? How serious and realistic is its declared objective to forge a 'strategic partnership' with Iran? What linkage, if any, is there between Putin's Iranian policies and the Moscow meeting with Hamas leaders? Finally, is it safe to conclude that Russia's interests and policies in that region are congruent with those of the West, or are they essentially at odds with each other?(SWP Comments / SWP)
Keywords: 320